Heavy metal content of over-the-counter toothpastes—a systematic review of in vitro studies - Kavery Chengappa; Ashwini Rao; Ramya Shenoy; Mithun Pai; Praveen Jodalli; Avinash BR (Frontiers in Dental Medicine)
BackgroundHeavy metal contamination of the environment has become a global problem because of their toxicity, environmental persistence, bioaccumulation, and biomagnification. The daily use of toothpastes containing heavy metals can be a threat to the environment since they can bioaccumulate and reach toxic proportions, affecting water, soil and living organisms.MethodsThis systematic review was performed to identify, assess, and compile information from the literature that looks into the possibility of heavy metals in toothpastes. The keyword search resulted in a total of 9,409 articles. After removal of duplicates, screening of titles and the abstracts, eleven studies that met the inclusion criteria were included. The quality of the studies was assessed using the Quality Assessment Tool for in vitro Studies (QUIN).ResultsAll eleven included studies reported the presence of heavy metals in one form or the other. This systematic review provides evidence for the presence of heavy metals in toothpastes from around the world.ConclusionsIn addition to being harmful to the consumer's health, these toothpastes are also harmful to the environment. Toothpaste containing heavy metals contributes to the already high level of heavy metal pollution in the environment from industrial and agricultural processes. There is a need for specific guidelines on the limits for heavy metals in toothpastes, with a clear distinction between essential and nonessential metals. More evidence from all parts of the world is needed to understand the gravity of the situation and to carry out remedial measures.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/V9P2D